Carbon in different phases ([CII], [CI], and CO) in infrared dark clouds: Cloud formation signatures and carbon gas fractions (Corrigendum) - Beuther, Henrik; Ragan, S. E.; Ossenkopf, V.; Glover, Simon; Henning, Th; Linz, H.; Nielbock, M.; Krause, O.; Stutzki, J.; Schilke, P.; Güsten, R. (Astronomy and astrophysics, 2015)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics